Tower Defense Game based on 2D Grid Using Goal-Based Pathfinding Method - Sahuri, Genta; Rosalina, Rosalina; Welly Tulili Panandu, Hardwin (International Journal of Management Science and Information Technology, 2023)
At the moment, agents cannot choose their own path with any flexibility in tower defense games. There may be a lot of enemies in one level of a tower defense game. The majority of in-game characters have a habit of moving in the direction of goals or objectives, though most have distinctive numbers and behaviors. The pathfinding method can be used to determine the route between the sources coordinates and the destination coordinates in an AI movement system. In this study, an objective-based pathfinding technique is used in a tower defense game where players can choose their own route. Based on the test results, the game can change the destination, which forces the adversary to alter their course to reach the new location. By placing units that can block these paths, this game also has the capacity to alter the available paths on the map.